Fatal child maltreatment in england. (4th April 2011) - Sidebotham, P; Bailey, S; Belderson, P; Brandon, M
Abstract : Aims: This paper presents comprehensive and up-to-date data covering 4 years of Serious Case Reviews into fatal child maltreatment in England. Methods: Information on all notified cases of fatal maltreatment between April 2005 and March 2009 was examined to obtain case characteristics related to a systemic classification of five broad groups of maltreatment deaths: severe physical assaults; overt homicide; infanticide and covert homicide; extreme neglect; deaths related to but not directly caused by maltreatment. Findings: A total of 276 cases were recorded giving an incidence of 0.63 cases per 100 000 children (0–18) per year. 246 cases could be classified based on the data available. Descriptive data suggest particular class characteristics of the different categories of death (table 1). The commonest specific group was those children who died as a result of severe physical assaults. Apparently deliberate overt and covert homicide was less common, while deaths as a direct consequence of neglect were rare. In contrast, some evidence of neglect was found in at least 40% of all cases, though not the direct cause of death. A large number of deaths appeared related to but not directly caused by maltreatment, these included sudden unexpected death in infancy where the cause of death was considered natural but in which there were associated concerns. Other related deaths included teenage suicide with evidence of previous maltreatment and accidental and natural deaths with evidence of poor parental care. Conclusions: These data provide a first attempt to systematically classify and describe characteristics of fatal maltreatment in England. Class characteristics differ between the different categories of death and may suggest the need for different strategies for prevention.